DEPENDENCE OF BENDING INFLEXIBILITY AND STRETCHING MODULE OF METAL CORD ON ITS TECHNICAL CHARACTERISTICS - O. A. Rjabtsev; A. V. Vedeneev (Литьë и металлургия, 2005)
The dependence of bending rigidity and stretching module of metal-cord of skeleton construction Jxdl+J8xd2 on its physical-mechanical characteristics is investigated.